Lec # 4 LAAG
Lec # 4 LAAG
Lec # 4 LAAG
[
= 9 10 9
−4 −4 −3
Now consider,
] ≠A.
−5 −6 −6 1 −2 −6
A 3 =A 2 A= 9
[ 10 9 −3 2
−4 −4 −3 2
9
0 −3 ][ ]
−5+18−12 10−12−0 30−54+18 1 −2 −6
[
= 9−30+18 −18+20+0 −54+90−27
−4+12−6 8−8−0 24−36+9 ] [
= −3 2 9 =A⋅¿ ¿
2 0 −3 ]
We observe that A 3=A , hence A is a periodic matrix having period 2.
2. Idempotent Matrix
2
A square matrix A is said to be Idempotent if A = A⋅¿ ¿
EXAMPLE: Show that
2 −2 −4
Solution: Consider
[
A= −1 3 4
1 −2 −3 ] is an Idempotent matrix.
[
= −1 3 4
1 −2 −3 ]=A
Since A2 = A, the given matrix A is an Idempotent Matrix.
NOTE:Identity matrix is always a periodic of period one. It is also an Idempotent matrix for I2 = I.
It may also be noted that an idempotent matrix is periodic matrix with period 1.
3. Nilpotent Matrix
k
A square matrix A is said to be nilpotent if A =O, k ∈N⋅¿ ¿
k
If k is the least member of N such that A =O , then k is called the “index” of A.
ab b 2
EXAMPLE: Show that
A= [ −a2 −ab ] is a nilpotent matrix of index 2.
Solution: Consider
ab b2 ab b2
A2=
[ −a2 −ab −a 2 −ab ][ ] ¿
ab3 −ab3
a2 b2−a2 b2
= 3 [3 2 2
−a b+a b −a b +a b2 2 =
0 0
0 0
=O⋅¿
][ ]
Since, A2 = O, the matrixA is a nilpotent matrix of index 2. You may observe that | A | = 0.
[ ]
−3 −4
−1 3 4
EXAMPLE:Show that 1 −3 −4 is nilpotent.
1 −3 −4
Solution: Let
[
A= −1 3 4
1 −3 −4 , then ]
1 −3 −4 1 −3 −4
[
A 2 =A⋅A= −1 3 4 −1 3 4
1 −3 −4 1 −3 −4 ][ ]
1+3−4 −3−9+12 −4−12+16 0 0 0
[
= −1−3+4 3+9−12 4+12−16 = 0 0 0 =O
1+3−4 −3−9+12 −4−12+16 0 0 0 ][ ]
Thus, the given matrix is nilpotent of index 2. You may observe that | A | = 0.
4. Involutory Matrix
A square matrix A is said to be Involutory matrix if A 2 =I⋅¿ ¿
0 1 −1
t t t
Hence ( AB ) =B A ⋅¿ ¿
Corollary: (A1A2 …An)t = Ant. … A2tA1t
2. Conjugate of a Matrix
A complex matrix obtained by replacing its elements by their corresponding complex conjugates is called the
2+3i 4 5i 2−3i 4
[ ] [ ]
−5i
A= 0 4i 8 , A= 0 −4i 8
4−3i 0 7+3i then
4+3i 0 7−3i is the conjugate matrix of A.
3. Tranjugate or Transpose of a Conjugate Matrix
The transpose of the conjugate of a matrix A is called the tranjugate or transposed conjugate of A. It is denoted by
( A ) t⋅¿ ¿ For example, if
3+4i 5−6i 2+3i 3−4i 5+6i 2−3i
6[
A= 4−5i 7 8i ,
5+6i 2−3i ] then
A = 4+5i
6 [ 7
5−6 i
−8i
2+3i ]
3−4i 4+5i 6
and
[
( A ) t = 5+6i 7 5−6i ⋅¿ ¿
2−3i −8i 2+3i ]
Properties of Tranjugate Matrix: If A and B are two complex matrices confirmable for addition and
multiplication, then
6. Hermitian Matrix
[
A= −1 0 −3 ,
−2 3 0 ] then
At= 1
[ 0 3
2 −3 0
=−
][
−1 0 −3 =−A⋅¿ ¿
−2 3 0 ]
__
t
A square matrix A for which ( A ) =A is called a Hermitian matrix. For example, if
a b−ic a b +ic
A=
[ b+ic d
,
] then
A=
[ b−ic d ]
and
( A )t =
[b+ica b−ic =A⋅¿ ¿
d ] So, A is a Hermitian matrix.
7. Skew-Hermitian Matrix
__
t
A square matrix A for which ( A ) =−A is called a skew-Hermitian matrix. For example, if
i 1−i 2 1+i 2
[ ] [ ]
−i
A= −1−i 3i i , A = −1+i −3i −i
−2 i 0 then
−2 −i 0
−i −1+i −2 i 1−i 2
t
[
( A ) = 1+i −3i −i =− −1−i 3i i =− A⋅¿ ¿
2 −i 0 −2 i 0 ][ ]
1 1+i 2+3i i 1+i 2−3i
EXAMPLE 01: If
[
A= 1−i
2−3i i
2 −i
0 ] and
[
B= −1+i 2i
−2−3i −1
1 ,
0 ] then show that
[
B= −1+i 2i
−2−3 i −1
1 ⇒iB= −i−1 −2
0 −2i+3 −i
i ⋅¿ ¿
0 ] [ ]
If iB is Hermitian, then it should satisfy the condition: ( iBt ) =iB⋅¿¿ Now,
__ −1 −i−1 −2i+3 −1 i−1 2i+3
iB = i−1 −2
2i+3 i [ −i = −i−1 −2
0 −2i+3 −i
i
0 ][ ]
−1 i−1 2i+3 −1 i−1 2i+3
[ ][ ]
__
t
∴(iB ) = −i−1 −2 i = −i−1 −2 i =iB⋅¿ ¿
−2i+3 −i 0 −2i+3 −i 0
Hence iB is Hermitian.
(ii) We have
1 1+i 2+3i 1 1−i 2−3i
[
A= 1−i 2
2−3i i
−i
0
⇒ A = 1+i 2
2+3i −i 0
i ⋅¿ ¿
] [ ]
Again, if A is Hermitian then it should verify the following condition: ( A )t ) =A⋅¿ ¿ Now,
______
1 1+i 2+3i 1 1−i 2−3i 1 1−i 2−3 i __
[ ][ ][ ]
__
t
( A) = 1−i 2 −i = 1+i 2 i ⇒ 1+i 2 i =A⋅¿ ¿
2−3i i 0 2+3i −i 0 2+3 i −i 0
Hence A is Hermitian.
(iii) We have
i 1+i 2−3i −i 1−i 2+3i
[
B= −1+i 2i
−2−3 i −1
1 ⇒B= −1−i −2i 1 ⋅¿ ¿
0 −2+3i −1 0 ] [ ]
t
If B is Skew – Hermitian then it should verify the following condition: −( B) )= B⋅¿ ¿ Now,
___________
−2+3 i 1−i 2+3i
[ ][ ]
__ −i −1−i −i __
t
− (( B ) ) = − 1−i −2i −1 = −1−i −2i 1 =B
2+3i 1 0 −2+3i −1 0
Hence, B is skew-Hermitian.
8. Orthogonal Matrix
A square matrix A is said to be orthogonal if AtA = I = A At
EXAMPLE 02: Show that the matrix
cosθ 0 sinθ
is orthogonal.
[ 0 1 0
sinθ 0 cosθ ]
Solution: By definition consider,
cos θ 0 -sinθ cosθ 0 sinθ
t
AA = 0
[
1 0 0 1 0
sinθ 0 cosθ -sinθ 0 cosθ
2 2
][ ]
cos θ+sin θ 0 cosθ sin θ−cos θ sin θ 1 0 0
=0
[ 1 0
2 2
cosθ sin θ−cos θ sin θ 0 cos θ+sin θ
= 0 1 0 =I
0 0 1
Similarly we can show that At A = I. Hence given matrix is orthogonal.
][ ]
NOTE: Since At A = IAt = A-1
−1 2 2
−1 2 2 −1 2 2
A=
1
3[ 2 −1 2
2 2 −1
⇒ A
t 1
=
3 ] [
2 −1 2 ⋅¿ ¿
2 2 −1 ]
Then
−1 2 2 −1 2 2 9 0 0 1 0 0
A t A=
[
1
9
t
2 −1 2 2 −1 2
2 2 −1 2 2 −1][
=
1
9
0 9 0
0 0 9
=
9
9 ][ ][ ]
0 1 0 =I⋅¿ ¿
0 0 1
Since, A A=I , therefore matrix A is orthogonal.
Theorem: If A andB are orthogonal matrices, then AB and BA are also orthogonal matrices.
Proof: Since A and B are orthogonal matrices, we have,AAt= I and B Bt= I. We have to prove that AB and BA are
also orthogonal.
Consider, (AB)(AB)t = AB. BtAt= A (B Bt)At= A(I) At= A At = I AB is orthogonal.
Similarly, consider (BA)(BA)t = BA. At Bt= B (BA At)Bt = B(I) Bt = B Bt = I BA is orthogonal.
9. Unitary Matrix
Now
1+i
2
[ ] [2
1−i
2
⇒A = 2
t
−1 +i
2
1−i
2
] [
2 ⋅¿ ¿
Also
( A )= 2
t
−1−i
2
2 ¿
1+i
2
]
1−i 1−i 1+i −1+i
(A )A= 2
t
−1−i
2
[ ][ 2
1+i
2
2
1+i
2
2
1−i
2
] ( )( )[
=
1
2
1 1−i
2 − ( 1+i )
1−i 1+i −1+i
][
1+i 1+i 1−i
Now let D = A - Atthen D t=(A - At ) t = At - (At ) t = At - A = -(A - A t ) = - D. Since D t= -D,hence D is skew-symmetric. But
D = A - At, hence A - At is skew-symmetric.
[ ] [ ]
7 9 5
t
5 4 5
t
12 13 10
t
A= 1 3 4 ⇒ A = 8 3 9 ∴ A + A = 9 6 13 and A− A = -7 0 -5
2 5 0 [ ] [ ]
We see that A + Atis a symmetric matrix and A – Atis skew-symmetric matrix. We also see that all the diagonal
elements of a skew-symmetric matrix are zero.
t t
3. If A is a square complex matrix, then A +( A ) is Hermitian and A−( A ) is skew-Hermitian matrix.
Proof: Let
________ ___ __ ____
¿t t __
t
−
( )
C=A+ ( A ) ⇒C = A + ( A ) =A + ( A ) = A +( A ) =A +A t
t
¿ ¿ ¿ ¿
[∵(A )=A ]
−t ¿ t −t
tt
() t
⇒ C =( A +A ) =( A ) + (( A) ) =( A ) +A=C. Since C =C, hence C is a Hermitian matrix.
t t ()
Now let,
________ ___ __
¿t ¿ ¿t ¿
−
( )
D=A− ( A )t ⇒D = A − ( A ) =A − ( A ) = A −( A ) =A −A t
t
¿
− t ¿ t
tt
(⇒ D) =( A −A ) =( A) − (( A) ) =( A )t−A=−( A−( A) )=−D.
t t t
Since,
t
( D ) =−D , hence D is a skew-Hermitian matrix.
4. If A be a Hermitian matrix, its diagonal elements are real. If A be a skew-Hermitian matrix, then its diagonal
elements are either zero or purely imaginary.
t
Proof: Let A be a Hermitianmatrix ( A ) =A . Now let its diagonal element be aii = α + i β. This
aii aii
implies that = α - i β. But aii = α + i β = α - i β 2 i β = 0 β = 0. Thus aii = a which is a real
number.
t
Let A be a skew-Hermitianmatrix ( A ) =−A . Now let its diagonal element be aii = α + i β. This implies that aij
= α - i β. But aij = - aii
α + i β = - ( α - i β ) α + i β = - α + i β 2 α = 0 α = 0.
Thus diagonal elements of Skew-Hermitian matrix are purely imaginary, that is, aii = i β. If
β = 0, then diagonal elements are zero.
05: If A and B be any two symmetric matrices then (AB) t = A B if and only if they commute.
Proof: Given that A and B are symmetric matrices, that is, At = A and B t = B.
Now let us assume that A and B commute, that is;
AB=BA (1)
B t At = A B
BA =AB [Because At = A and Bt = B]
i 2-3i 4+5i
A = 6+i 0 4-5i
-i 2+i
EXAMPLE 02: Express 2-i
as the sum of Hermitian and skew – Hermitian matrices.
Solution: We have
1 i 2 5 5i 1 i 2 5 5i
A 2i 2 i 4 2i , A 2i 2 i 4 2i
1 i 4 1 i 4
7
7
1 i 2i 1 i
A t 2 2 i 4
5 5i 4 2i
7
Thus,
1 i 2 5 5i 1 i 2i 1 i 2 22i 46i
t 2i 2 i 4 2i 2
A A 2i 4 2 2i 4 2i
1 i 4
7 4 6i 2i
7 5 5i 4 2i 14
1 1i 23i
1
2 t
A A 1i
2 i
23i i 7
(i)
Similarly,
1+i 2 5−5 i 1−i −2 i −1−i 2i 2+2i 6−4 i
A−( A ) =
t
[ 2 i 2+i 4 +2i − 2
−1+i −4 7
2−i
5+5 i 4−2 i][
−4
7 ] [ = −2+2i 2i
−6−4 i −8+2i
8+2i
0 ]
i 1+i 3−2i
1
2
{ A−( A ) t } =
[ −1+i i
−3−2i −4+i
4+i
0 ] (ii)
Adding (i)and(ii), we have
1 1−i 2−3i i 1+i 3−2 i
1
2
Hermitian Matrix
{ A+ ( A ) t }+ 1
2
t
[
{ A−( A ) }= A= 1+i 2
2+3i −i
Skew – Hermitian Matrix
7
i + −1+i i
][
−3−2 i −4 +i
4+i ⋅¿ ¿
0 ]
1.7 PARTITIONING OF MATRICES
Definition: A matrix obtained by deleting some of the rows and columns of a matrix A is said to be
sub- matrix of matrix A.
4 1 0
For example, if
[ ]
A= 5 2 1 ,
6 3 4 then
4 1
[ ] ,[ ]
5 2
5 2
6 3 and
1 0
[ ]
2 1 are sub-matrices of A.
Definition: Partitioning
A matrix may be subdivided (partitioned) into sub matrices in many different ways and the manner in which it is to
be partitioned is often indicated by a system of horizontal and vertical dotted lines. Calculation of matrices can be
greatly simplified if given matrices are represented as blocks of sub matrices, to be treated as elements of the
given matrices. The order of sub matrices is to be so chosen that the addition, subtraction and products between
them must be confirmable. For example, let
2 1 0 4 1
[
A= 1 0 2 3 4
4 5 1 6 5 ]
It may be5 partitioned as under:
2 1 ⋮ 0 4 1
A=
[1
⋯
4
0
⋯
5
⋮
⋮
⋮
2
⋯
1
3
⋯
6
4
][
⋯ A
5
A
= 11
21
A12
A22
,
] where
A 11=
[21 10 ] is a 2×2 sub matrix,
A 12=
[02 4 1
3 4 ] is a 2×3 sub matrix,
matrices
A ij and
B ij of the two matrices are of the same order. For example,
−1 4 ⋮ 3 a b ⋮ c
A=
[
⋯ ⋯ ⋮ ⋯ A 11
6 −1 ⋮ 0
−7 8 ⋮ 2
=
A 21
Moreover,
A 11+B 11 , A 12 +B12 , A 21 +B21 , and
A 22 +B22 are all defined. We have
−1+a 4+b ⋮ 3+c
A +B=
A=
1 0 0
[
0 1 0
2 −3 1
2 −4 3
0
0
3
7
0
0
5
6
and
]
partitioned blocks for A and B to calculate AB.
[ ]
3 −4
B= 0 5
6 1
−2 1
be matrices of order 4 ×5 and 5 × 2 respectively. Use suitable
1 2
[
1 0 0 ⋮ 0
0 1 0 ⋮ 0
A= ⋯ ⋯ ⋯ ⋮ ⋯
2 −3 1 ⋮ 3
2 −4 3 ⋮ 7
whereJ, O, L, M, P and Q are of suitable orders.
0
0
⋯=
5
6
]J O
L M[ ]
and
B=
[ ]
3 −4
0
⋯ ⋯
6
−2 1
5
1
P
= ,
Q []
Then
AB=
[ JL MO ][QP ]=[LPJP+OQ
+MQ ] (i)
Now
1 2
JP= [ 1 0 0
0 1 0
3 −4 =
0 5
][
1 2
3 −4
,
][ ] OQ=
0 0 6 1 0 0
[ ][ ] [ ]
=
0 0 −2 1 0 0
,
1 2
LP=
2 −3 1
[
2 −4 3
3 −4 =
0 5
−7 21
−10 35
, ][ ] [ ] and
MQ=
[37 56 ][−26 11 ]=[308 138 ]⋅¿ ¿
Therefore,
JP+OQ=
[13 −42 ]+[00 00 ]=[13 −42 ] and
LP+MQ=
[−10−7 2135 ]+[308 138 ]=[201 2948 ]⋅¿ ¿
Hence from(i), we have
1 2
1 −1 0
AB=
3
1
20
[ ] −4
29
48
⋅¿ ¿
where
X= ][
1 −1
−1 1
0 ]
,O= ,Y =[ 1 −1 ]
0 [
and Z= [−2]⋅¿ ¿
] []
X O X O X2 O
Then
A=
2
[ ][ ] [
=
Y Z Y Z YX+ZY Z 2
⋅¿ ¿
] (i)
Now
2
X =X⋅X=
[−11 −11 ]⋅[−11 −11 ]=[−22 −22 ]=2[−11 −11 ]=2 X , (ii)
X2 O X2 O X 2 O X4 O
A=
2
[ ]
O Z2
, [ ][ ] [
4
A =( A ) =
22
O Z2 O Z 2
=
O Z4
,
] and
4 4 8
X O X O X O
8 4 2
A =( A ) =
[ ][ ] [ ] ¿ ¿
O Z4 O Z 4 =
O Z8
⋅